Between normative universality and sharing embodied knowledge–exploring the (re-) definition of legitimate knowledge and knowers using the example of the German public media debate about racism - Weiß, Ana-Nzinga (Frontiers in Sociology, 2025)
This article seeks to present a new approach to studying the dynamics of constructing legitimate knowledge and speaker positions in public media discourse that is characterized by a hybrid media system. The basic framework of this approach is built on the paradigm of social epistemology and the presumption that although knowledge can be shared, the conditions of sharing are subject to social power structures. By conceptualizing the media as part of social epistemological processes, I offer a conceptual innovation that allows for a nuanced and critical analysis of how inequalities can be (re)produced in media representation. Within the context of the German public debate about racism since the Black Lives Matter protests in the summer of 2020, I analyzed talk shows on the topic of racism that aired on German public television, YouTube, and Instagram by means of a Critical Discourse Analysis as a means of illustrating analysis within this framework. My analysis revealed three patterns through which it was possible to construct legitimate knowledge and speaker positions about racism: (1) performances of a rational and equitable exchange of opposing epistemic positions, (2) performances of counter-hegemonic positionality in communal exchange, and (3) performances of a rational exchange of embodied knowledge. The results illustrate the delicate interplay of different power structures within the construction of knowledge regarding racism. I conclude with an emphasis on the need for a parrhesian praxis in social analysis in service of being constantly self-critical and, at the same time, critical of power.